Study on Bank Slope Stability of Fully-Strongly Weathered Phyllite Bridge Soaked in Reservoir Water - TANG Gang; LIAO Jun; DENG Tao; WANG Chenbin; XIE Ming; WANG Ruilin; LI Jing (Renmin Zhujiang)
Fully-strongly weathered phyllite has strong water sensitivity,and the physical and mechanical properties of the phyllite will inevitably deteriorate after it is soaked in reservoir water,which is extremely unfavorable to the stability of the bank slope.In view of this,taking the bank slope of a fully-strongly weathered phyllite bridge as the research object,this paper carries out detailed field investigations,indoor physical and mechanical tests,and Geo-Slope software analysis,considers the effect of reservoir water storage on the deterioration of the shear strength of the phyllite on the bank slope,and calculates the variation law of the stability of the bank slope of the bridge.The results show that the shear strength parameter and the safety factor of the bank slope of the fully-strongly weathered phyllite decrease greatly within a short time after the reservoir is impounded,but the decrease then gradually slows down.In addition,after the reservoir is impounded,the deterioration of cohesion is larger than that of the angle of internal friction,and the water sensitivity of the cohesion is stronger.When the bank slope is soaked in water for 95 days,the safety factor is calculated to be 1.189,which is less than 1.200 and indicates an under-stable state.Therefore,measures to reinforce the bank slope are proposed.